Abrapalabra: in the learning of reading and writing for second-grade children with educational needs - DIAZ QUENGUAN, WASHINGTON; Morán Borja , Lila Maribel; García Cobas , Rudy (Revista Minerva, 2025)
ABSTRACT Our research clearly shows that the use of Abrapalabra as a teaching tool to improve literacy in second-grade children with special educational needs designs knowledge in an environment of interactive and gamified elements. The small study conducted highlights the barriers to learning and offers strategies for student participation, socialization, and motivation within educational settings and their own practices. Currently, the incorrect use of technological tools further confuses children with special educational needs, and their attention can be focused primarily on visual and auditory aspects. This study is purposeful and based on the analysis of the impact of the Abrapalabra tool on improving these skills. To this end, a mixed approach was adopted based on a quasi-experimental design with pretests and posttests in the intervention group of the study. The sample consisted of 21 students, 23.81% of whom were students with special educational needs, 6 teachers, and 21 parents. Surveys, interviews, diagnostic tests, and systematic observations were used to analyze reading skills, motivation, and socialization. The conclusions drawn included a significant increase in literacy, writing, and reading comprehension, as well as increased student motivation and greater social integration in the classroom. Teachers, parents, and experts highlighted in their statements the usefulness of Abrapalabra in promoting inclusive, motivating, and effective education, particularly for students with special educational needs.